2020
DOI: 10.3390/nano10050942
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorod Assemblies: The Roles of Hot-Spot Positioning and Anisotropy in Plasmon Coupling and SERS

Abstract: Plasmon-coupled colloidal nanoassemblies with carefully sculpted “hot-spots” and intense surface-enhanced Raman scattering (SERS) are in high demand as photostable and sensitive plasmonic nano-, bio-, and chemosensors. When maximizing SERS signals, it is particularly challenging to control the hot-spot density, precisely position the hot-spots to intensify the plasmon coupling, and introduce the SERS molecule in those intense hot-spots. Here, we investigated the importance of these factors in nanoassemblies ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In terms of specic nano-assembly morphologies, core-satellite nanoassemblies demonstrate stricter control over their number of NP-NP junctions i.e., hot-spot density and thus plasmon coupling. Such core-satellite morphologies have been reported using branched polymeric linkers with spherical core, 103 with DNA linkers utilizing gold nanorods as the core, 72,104 as well as with more complicated structures of caged gold nanorods as core. 105 Recently, Dey et al 91 have reported a distinct morphology of core multi-tentacle assemblies that provides the unique features of both core-satellites and branched nanochains.…”
Section: Key Design Considerations Of Gold Nanostructure Contrast Agentsmentioning
confidence: 77%
“…In terms of specic nano-assembly morphologies, core-satellite nanoassemblies demonstrate stricter control over their number of NP-NP junctions i.e., hot-spot density and thus plasmon coupling. Such core-satellite morphologies have been reported using branched polymeric linkers with spherical core, 103 with DNA linkers utilizing gold nanorods as the core, 72,104 as well as with more complicated structures of caged gold nanorods as core. 105 Recently, Dey et al 91 have reported a distinct morphology of core multi-tentacle assemblies that provides the unique features of both core-satellites and branched nanochains.…”
Section: Key Design Considerations Of Gold Nanostructure Contrast Agentsmentioning
confidence: 77%
“…Nanorods of gold are known to exhibit two plasmon bands, one most intense at longer wavelengths, that corresponds to the polarization of conduction electrons along the main rod axis, and a second resonance, less intense, located at a similar wavelength as in nanospheres, due to polarization along the short axis [ 16 , 17 , 40 , 61 ]. The spectral location of the main resonance is tuneable by changing the aspect ratio of the rod, i.e., the ratio between the main and the minor axis [ 16 , 17 , 40 , 61 , 62 ]. It should be noted that asymmetric NPs can bind the latex moiety with a different orientation and, for the AuNR, we considered the two limiting cases of longitudinal or transversal binding along the dimer axis.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 a–d show that as the Ag sputtering power increased, the PS surface roughness gradually increased, which is caused by the growth and nucleation of Ag during the sputter deposition process [ 23 ]. Gaps between the microspheres were gradually filled, which will strongly affect the position and intensity of “hot spots” in the ordered array [ 24 ]. In addition, the elemental distribution of Ag, Zn, and O covering PS was confirmed by SEM elemental mapping, indicating that the relative content of each element in the composite film material changed with increasing Ag sputtering power.…”
Section: Resultsmentioning
confidence: 99%